ĐẶC ĐIỂM RỐI LOẠN LO ÂU LAN TỎA Ở NGƯỜI BỆNH PHỔI TẮC NGHẼN MẠN TÍNH (Vietnam Journal of Community Medicine, 2026)
Problem Statement: This study investigates the clinical manifestations of generalized anxiety disorder (GAD) in patients with COPD, highlighting the overlapping symptoms that complicate diagnosis and treatment.Study Objective: To describe the clinical characteristics of GAD in patients with COPD.Subjects and Methods: A cross-sectional descriptive study was conducted on 163 patients diagnosed with chronic obstructive pulmonary disease (COPD) who were examined and treated at Hanoi Lung Hospital in 2025-2026.Research Results: The prevalence of GAD in patients with COPD was 28.8%, higher in females (43.2%) than in males (24.6%), with statistically significant differences (p